2015
DOI: 10.15446/ing.investig.v35n2.50019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the rheological response of reconstituted gastric mucin

Abstract: The rheological response of reconstituted gastric mucin was studied by time dependent rheological experiments as function of pH. Mucin concentrations of 5 % and 10 % were prepared in buffer dispersions at pH of 1.15, 2.00, 2.55, 4.00 and 7.67. The isoelectric point was identified by z-potential between pH 2.00 to 2.55. Dynamic light scattering showed that as pH reduced, a second population of larger mucin aggregates was formed indicating the presence of new structures. Steady shear rheological measurements ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
(28 reference statements)
1
10
0
Order By: Relevance
“…The response of native mucus [including porcine gastric, intestinal, duodenal, and colonic mucus (Nordgård & Draget 2015;Philippe et al 2017;Sellers et al 1983Sellers et al , 1988Taylor et al 2003); equine respiratory mucus (Gross et al 2017); human saliva (Stokes & Davies 2007; cervical mucus (Critchfield et al 2013); and cervicovaginal mucus (Wang et al 2013)] under SAOS is predominantly solid like [storage or elastic modulus (G ) > loss or viscous modulus (G )], with slowly varying dependencies of both G and G on the oscillation frequency. Similar broad-spectrum responses were also observed during creep compliance measurements performed on Sigma-Aldrich mucin gels (Caicedo & Perilla 2015) and during stress relaxation experiments in native porcine gastric mucus (Philippe et al 2017).…”
Section: Stiffnesssupporting
confidence: 62%
“…The response of native mucus [including porcine gastric, intestinal, duodenal, and colonic mucus (Nordgård & Draget 2015;Philippe et al 2017;Sellers et al 1983Sellers et al , 1988Taylor et al 2003); equine respiratory mucus (Gross et al 2017); human saliva (Stokes & Davies 2007; cervical mucus (Critchfield et al 2013); and cervicovaginal mucus (Wang et al 2013)] under SAOS is predominantly solid like [storage or elastic modulus (G ) > loss or viscous modulus (G )], with slowly varying dependencies of both G and G on the oscillation frequency. Similar broad-spectrum responses were also observed during creep compliance measurements performed on Sigma-Aldrich mucin gels (Caicedo & Perilla 2015) and during stress relaxation experiments in native porcine gastric mucus (Philippe et al 2017).…”
Section: Stiffnesssupporting
confidence: 62%
“…To test if the dye-protein interaction is somehow dependent by the hydrophobic domains of mucin we recorded the emission of squaraines in presence of PGM at pH 2. It is known that at acidic pH, the hydrophobic domains of mucin are involved in non-covalent crosslinks via hydrophobic associations [3,40]. As can be seen in Figure 5, at acidic pH the emission intensity of the squaraines in presence of mucin is reduced.…”
Section: Spectroscopic Measurementsmentioning
confidence: 91%
“…These formulations resulted in positively charged chitosan nanoparticles, which should facilitate electrostatic interactions with the negatively charged carboxylic acid groups of the mucin. Studies on native pig gastric mucin have previously shown an isoelectric point at ∼pH 2-2.5[39] and sialic acid has a pKa of 2.6[40]. Therefore, there is potential to interact with the positive charged amino groups of chitosan nanoparticles[41] when both sialic acid and chitosan are oppositely charged at therefore ~ pH 4.5 -5.…”
mentioning
confidence: 99%